Kebijakan Kawasan Industri (Bantaeng Industrial Park) Di Kabupaten Bantaeng - Alam, Syamsul; Madani, Muhlis; Abdi, Abdi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this study was to determine how the implementation of policies and factors that influenced the development of industrial estates (Bantaeng Industrial Park) in Pa'jukukkang District, Bantaeng Regency. The type of research used qualitative with a phenomenological type. The number of informants was 9 people. Data collection techniques used observation, interviews with a number of informants. Data analysis used interactive analysis models. The results showed that the industrial estate policy (Bantaeng industrial park) in Bantaeng Regency had not been fully implemented optimally in accordance with its objectives, this was seen from the indicators (1) Administrative aspects in this case PT. Huadi Nickel has carried out the administrative process that they were supposed to do, but in the course of a number of elements violated the administrative requirements, (2) Technical aspects because it could be without technical requirements, the workers would be overwhelmed while doing their jobs, (3) Environmental aspects in terms of PT. Huadi Nickel was only a mere formality because it pollutedthe sea which was used as the livelihood of fishermen and seaweed farmers, (4) Financial Aspects of PT. Huadi had a major impact on the survival of residents and farmers, especially seaweed farmers.Keywords: Industrial Estate Policy (Bantaeng Industrial Park)